Evaluation of Bokashi Compost Phytotoxicity on Seeds of Some Selected Arable Crops using Heavy Metals and Germination Bioassay Test - Gashua, Auwalu Garba; Ibraheem, Alhassan; Jawa, Isiyaku Grema; Ibrahim, Samira; Jirgi, Ibrahim Abdullahi; Oluwatayo, Aregbesola Babatunde (Sahel Journal of Life Sciences FUDMA, 2025)
Correction